Recurrent Acute Upper Limb Ischemia in a Young Male: Case Report - Widya Safitri; Suci Indriani; Suko Adiarto (Interna Publishing, 2024)
Although acute upper limb ischemia (AULI) is less prevalent than lower acute limb ischemia, AULI may lead to severe morbidity if not well-treated. To manage AULI appropriately, evaluation of the etiologies, risk factors, and revascularization is of importance. Here we present a case of recurrent AULI and its appropriate diagnostic and management approaches. A 27-year-old male with a chief complaint of pain and numbness in his left arm for one week. He had a history of AULI seven months before and was treated by percutaneous intra-arterial thrombolysis at left brachial and radial arteries with residual non-occlusive thrombus. Duplex ultrasound (DUS) and CT angiography revealed a new soft thrombus with occlusion at the left subclavian artery. Evaluation of comorbid risk factors and source of thrombus was performed. The patient underwent pharmacomechanical thrombectomy and angioplasty procedure. The diagnosis of AULI was established based on pain and numbness in the left arm, and the finding of soft thrombus and occlusion of the left subclavian artery on DUS and CT angiography evaluation. Although various workups have been carried out to determine the etiology of AULI in this patient, the definite cause remains unknown. In addition, pharamcomecanical thrombectomy and angioplasty were performed as the appropriate revascularization methods in this condition. Recurrent AULI is a rare vascular phenomenon leading to disabling morbidities and fatal consequences if not treated properly. Further evaluation of etiology and risk factors for recurrent AULI is mandatory for appropriate management besides revascularization.